Antiretroviral effect of lovastatin on HIV-1-infected individuals without highly active antiretroviral therapy (The LIVE study): A phase-II randomized clinical trial (2009)
ABSTRACT: Background: Highly active antiretroviral therapy produces a significant decrease in HIV-1 replication and allows an increase in the CD4 T-cell count, leading to a decrease in the incidence of opportunistic infections and mortality. However, the cost, side effects and complexity of antiretroviral regimens have underscored the immediate need for additional therapeutic approaches. Statins exert pleiotropic effects through a variety of mechanisms, among which there are several immunoregulatory effects, related and unrelated to their cholesterol-lowering activity that can be useful to control HIV-1 infection. Methods/design: Randomized, double-blinded, placebo controlled, single-center, phase-II clinical trial. One hundred and ten chronically HIV-1-infected patients, older than 18 years and naïve for antiretroviral therapy (i.e., without prior or current management with antiretroviral drugs) will be enrolled at the outpatient services from the most important centres for health insurance care in Medellin-Colombia. The interventions will be lovastatin(40 mg/day, orally, for 12 months; 55 patients) or placebo (55 patients). Our primary aim will be to determine the effect of lovastatin on viral replication. The secondary aim will be to determine the effect of lovastatin on CD4+ T-cell count in peripheral blood. As tertiary aims we will explore differences in CD8+ T-cell count, expression of activation markers (CD38 and HLA-DR) on CD4 and CD8 T cells, cholesterol metabolism, LFA 1/ICAM-1 function, Rho GTPases function and clinical evolution between treated and not treated HIV-1-infected individuals. Discussion: Preliminary descriptive studies have suggested that statins (lovastatin) may have anti HIV-1 activity and that their administration is safe, with the potential effect of controlling HIV-1 replication in chronically infected individuals who had not received antiretroviral medications. Considering that there is limited clinical data available on this topic, all these findings warrant further evaluation to determine if long-term administration of statins may benefit the virological and immunological evolution in HIV-1-infected individuals before the use of antiretroviral therapy is required.